The Effect of foniks*PINTAR Method on Emergent Literacy Skill of Preschool Children. - Kusumawardhani, Trully; Dhieni, Nurbiana; Yetti, Elindra (Sekolah Pascasarjana Universitas Negeri Jakarta, 2024)
Academic success is closely related to children's reading ability at school age. Subsequently, reading ability is largely determined by emergent literacy skills at preschool age. Considering the low national Indonesian student literacy skills ranked at the bottom layer of PISA international assessments, it becomes necessary to set up strategic methods to enhance children's emergent literacy at preschool age. There is no standardized method of teaching pre-reading ability in Early Childhood Education in Indonesia. Phonological awareness plays a significant role in reading ability, working memory, language skills, and letter knowledge. This article is part of a thesis that aims to see the effect of the foniks*PINTAR method based on phonics on the emergent literacy skills of kindergarten children. This is a qualitative study with literature research using PubMed and Google Scholar search engines with keywords phonological awareness, emergent literacy, phonics method, and foniks*PINTAR. Thirty-five relevant articles were obtained after following the inclusion and exclusion criteria of the research.It was concluded that research is required to see the effect of the foniks*PINTAR method, which is a structured, systematic, and multisensory phonics-based method on the emergent literacy skill of preschool-aged children.